Infection and treatment method (ITM) vaccine against East Coast fever: Reducing the number of doses per straw for use in smallholder dairy herds by thawing, diluting and refreezing already packaged vaccine - Patel, Ekta; Mwaura, Stephen; Giulio, Giuseppe di; Cook, Elizabeth A.J.; Lynen, Godelieve; Toye, Philip G. (Springer, 2019)
The Infection and Treatment Method (ITM) of vaccination is the only immunization procedure currently available to protect cattle against East Coast fever (ECF), a tick-transmitted disease responsible for losses of several hundreds of millions of dollars per year in sub-Saharan Africa. The vaccine comprises a homogenized preparation of infected ticks packaged in straws and stored in liquid nitrogen. The current manufacturing protocol results in straws containing 30-40 doses (ILRI 0804), which is impractical for immunizing small herds as found in dairy and smallholder farming systems. The ILRI 0804 SD stabilate was prepared as a 1:5 dilution of the parent stabilate, with the aim of producing vaccine stabilate straws containing between four to eight doses and thus suitable for smallholder farming systems. Infectivity of the diluted stabilate was assessed and the protective efficacy of the diluted stabilate was determined by performing experimental and field immunizations.Two groups of six cattle were inoculated with 1 ml of the diluted stabilate at 1:20 (equivalent to the recommended field dose for ILRI 0804, assuming no loss of sporozoite viability during thawing and refreezing) and 1:14 (assuming 30-35% loss of sporozoite viability). Schizonts were detected in all 12 animals, showing viability of sporozoites. Ten animals from the infectivity study and two control animals not previously exposed to T. parva were challenged with the parental ILRI 0804 stabilate. The results show that the two control animals displayed severe ECF reactions and were treated 14 days after challenge. Of the previously infected animals, only one underwent a severe reaction following challenge, a result in accord with the challenge experiments performed previously with the parent stabilate [Ticks Tick-Borne Dis 7:306-314, 2016]. The animal that displayed a severe reaction had no detectable schizonts and did not seroconvert following the initial inoculation with ILRI 0804 SD. In addition, 62 animals immunized under field conditions showed a mean seroconversion rate of 82%.The results presented in this article demonstrate that it is possible to prepare straws suitable for use in smallholder herds by thawing, diluting and refreezing already packaged vaccine.